Degradation of proteins by PROTACs and other strategies - Yang Wang; Xueyang Jiang; Feng Feng; Wenyuan Liu; Haopeng Sun (Elsevier, 2020)
Blocking the biological functions of scaffold proteins and aggregated proteins is a challenging goal. PROTAC proteolysis-targeting chimaera (PROTAC) technology may be the solution, considering its ability to selectively degrade target proteins. Recent progress in the PROTAC strategy include identification of the structure of the first ternary eutectic complex, extra-terminal domain-4-PROTAC-Von-Hippel-Lindau (BRD4-PROTAC-VHL), and PROTAC ARV-110 has entered clinical trials for the treatment of prostate cancer in 2019. These discoveries strongly proved the value of the PROTAC strategy. In this perspective, we summarized recent meaningful research of PROTAC, including the types of degradation proteins, preliminary biological data in vitro and in vivo, and new E3 ubiquitin ligases. Importantly, the molecular design, optimization strategy and clinical application of candidate molecules are highlighted in detail. Future perspectives for development of advanced PROTAC in medical fields have also been discussed systematically. KEY WORDS: Protein degradation, PROTAC, Ubiquitin−proteasome system, E3 ubiquitin ligase, Target protein, Heterobifunctional molecule